Cell chirality exhibition of brain microvascular endothelial cells is dependent on micropattern width. Issue 46 (21st October 2022) - Porras Hernández, Ana María; Tenje, Maria; Antfolk, Maria
Abstract : Brain endothelial microvascular cell chirality is dependent on micropattern width and spatial localization. Finding the optimal micropattern width and including only the centre cells in the analysis for chirality-based experiments might improve further experimental results. Abstract : Left-right asymmetry is a conserved property in nature and observed in the human body, a property known as cell chirality. Cell chirality is often studied using micropatterned in vitro models. However, micropattern geometry and size often varies across different studies, making it challenging to compare results. Here, we utilized micropatterned RGD-peptide lines on hyaluronic acid hydrogels to investigate the effect of the micropattern width on the exhibited cell chirality bias of brain microvascular endothelial cells. Overall, this cell type exhibited a negative chirality bias on micropatterned lines ranging from 10 μm to 400 μm in width, where the negative bias was most pronounced on the 100 μm wide lines. We also observed that this exhibited chirality bias varied across the line width. This work serves as a guide to determine optimal micropattern width for further investigations on cell chirality bias and its prominence in e.g., disease states or upon exposure to toxic substances.